Experimental evaluation of extra-stroke displacement capacity for Curved Surface Slider devices. Issue 146 (July 2021) - Furinghetti, Marco; Yang, Tianye; Calvi, Paolo Martino; Pavese, Alberto
Abstract: Curved Surface Slider (CSS) devices have been widely used in recent years for the reduction of seismic vulnerability of structural systems. Recent risk assessment studies have revealed that base isolated systems can be characterized by higher seismic risk with respect to their fixed-base counterparts. It is believed that this unexpected outcome is, partly, due to the definition of collapse condition that has traditionally been adopted for base isolated structures, which is somewhat stricter than for many other structural systems. More specifically, in most circumstances, a base isolator is assumed to collapse once the sliding pad reaches maximum geometrical displacement, which corresponds to the edge of the sliding surface. This paper summarizes the results of an experimental program that investigated the response of CSS devices under extreme seismic loading, with focus on base isolation devices stressed beyond their nominal capacity. A full-scale Double CSS prototype with three different low-friction materials was tested with cyclic signals and in the context of a hybrid simulation. A low value of peak sliding velocity has been assumed, in comparison to realistic values experienced during earthquake excitations, in order to be able to control the stability of the force response for the whole duration of the performed tests. The results collected were able to assess the effective response of CSS devices, when design geometrical characteristics are overcome within specific defined limits, and to formulate suitable numerical models to deal with extra-stroke response of DCSS in dynamic analysis. Highlights: Concave Surface Slider devices can be subjected to extra-design displacements. The experimental response of CSS devices under extra-design displacements is stable. The proposed numerical models can capture the extra-stroke behavior of CSS devices. Extra-design displacements of CSS devices provide a lower risk level of structures.